PREVENTION OF CANCER OF THE CERVIX UTERI AT AN ANTENATAL CLINIC - I. E. Bakhlaev; P. I. Kovchur (ABV-press, 2014)
Cervical cancer (CC) morbidity is analyzed on the basis of the data of the Karelian cancer register over the period 1998-2007. During this period, 816 cases of CC were registered and 126 were found at an antenatal clinic (AC). Its early detection rate was ascertained to be 96% during screening at the AC. A comprehensive examination was made in 1742 women with various cervical diseases, of them 37.5% were infected with human papillomavirus (HPV). High-grade dysplasia and carcinoma in situ were diagnosed in 6.6% of the HPV-infected patients. Large-scale screening for HPV infection and pretumor disorders with their further treatment will aid in reduc- ing CC morbidity and mortality rates.